(untitled) (Research, Society and Development, 2024)
Introduction: Breast cancer, one of the most prevalent neoplasms among women, although it can also affect men to a lesser extent, continues to be a significant public health challenge. Despite advances in early diagnosis and therapies for primary breast cancer, treatment options for metastatic disease remain limited, with reduced effectiveness. A deeper understanding of the mechanisms driving metastasis and therapeutic innovations has driven important changes in the management of the disease. Aim: To review the main biological mechanisms involved in breast cancer bone metastasis, with emphasis on the molecular, genetic, and cellular factors that facilitate tumor dissemination. Methodology: Using the PICO strategy, a systematic search was conducted in databases such as Biblioteca Virtual em Saúde and PubMed, covering publications from January 2013 to September 2024. The analysis focused on the relationship between breast neoplasia and factors predisposing to bone metastasis. Results: The study analysis considered the year of publication, research location, study type, and key findings. The data indicated the need for further exploration of the biological mechanisms of bone metastasis, highlighting factors that promote tumor dissemination, revealing the complexity of healthcare management. Conclusion: Breast cancer metastasis is a complex process, with the interaction between tumor cells and the stroma playing a crucial role at each stage of metastatic dissemination. In bone metastasis, in particular, tumor cells alter the bone microenvironment, promoting destruction and facilitating their proliferation.